Peran Masyarakat dalam Membentuk Kesadaran Sosial di Era Digital - Ahmad Luhi Sanusi Wijaya; Sheril Febriyati; Elfira Rizki Utami; Agniatun Nisa; Novia Nasya Hartini (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
The rapid development of digital technology has significantly transformed the way society forms social awareness. This study aims to analyze the role of society in shaping social awareness in the digital era, identify supporting and inhibiting factors, and formulate strategies to optimize community participation through digital technology. This research employed a qualitative approach using a descriptive-library research method by reviewing national scientific journals published between 2021–2024. Data analysis was conducted descriptively-analytically with source triangulation to ensure credibility. The findings reveal that social media and digital platforms have become primary catalysts that transform individuals from passive information consumers into active producers of social narratives, as evidenced by the emergence of digital social movements that transcend geographical boundaries. However, the digital era also presents serious challenges, including the spread of hoaxes, hate speech, disinformation, and social polarization. Digital literacy emerged as a crucial factor determining the quality of community participation in digital spaces. Furthermore, cultivating tolerance, empathy, and social values are key pillars in building healthy social awareness within Indonesia's multicultural society. This study concludes that strengthening digital literacy, active family involvement, and cross-sector collaboration are essential strategies to optimize the community's role in fostering constructive social awareness in the digital era..